Application of Interactive Multimedia Based on Microsoft Power Point to Increase Students' Interest in Learning in Civics Learning in Class VIII B of SMP Negeri 3 Balaesang - Nurhaliza, Sitti; Sukmawati, Sukmawati; Imran, Imran; Nasran, Nasran; Kulyawan, Roy; Jamaludin, Jamaludin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research focuses on the application of interactive multimedia based on Microsoft Power Point to increase students' interest in learning Civics in class VIII B of SMP Negeri 3 Balaesang. The subjects of this research were 25 students from class VIII B who took Civics subjects. The type of research used is classroom action research (PTK) which consists of II cycles. The research design follows the research stages which refer to the Kemmis and McTaggart model, namely: (1) planning stage, (2) implementation stage, (3) observation stage, (4) reflection stage. Data collection techniques in this research were carried out using observation sheets, interviews and documentation. The results of the research show that the application of interactive multimedia based on Microsoft PowerPoint can increase students' interest in learning from cycle I to cycle II, namely teacher activity obtained from 50% increased to 83.33% and was included in the very good category. Based on observations of student activities in cycles I and II, it was found that there was an increase, where in cycle I students who got a score of 1 were more dominant than students who got a score of 4, whereas in cycle II there were no more students who got a score of I. There were even several students who got a score. 4.